Research on differential properties of Keccak-like nonlinear transform - Qian-nan LI; Yun-qiang LI; Shu-jing JIANG; Yao LU (Tongxin xuebao)
By analyzing the nonlinear transformation in Keccak,n-gram Keccak-like nonlinear transform model was proposed firstly,and the differential properties of this kind of transformation was studied.They are proved that to the n-gram Keccak-like nonlinear transform,the differential transition probability about cycle shift transform is unchanged,and nonzero differential transition probabilities are equal when the input difference was confirmed.The range of the dif-ferential transition probability was calculated when it wasn't 0 and 1.By analyzing the Boolean expressions of the output difference,the differential construction for largest nontrivial and smallest nonzero differential transition probability were obtained.At the end,one correlation between the differential probabilities of adjacent variable in n-gram Keccak-like nonlinear transform was given.